Functional characterization of a novel aminoglycoside phosphotransferase, APH(9)-Ic, and its variant from Stenotrophomonas maltophilia - Shi, Weina; Lu, Junwan; Feng, Chunlin; Gao, Mengdi; Li, Anqi; Liu, Shuang; Zhang, Lei; Zhang, Xueya; Li, Qiaoling; Lin, Hailong; Lin, Xi; Li, Kewei; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
In this work, we characterized a novel aminoglycoside (AG) resistance gene designated aph(9)-Ic from S. maltophilia 142. Among all the function-characterized resistance genes, APH(9)-Ic shares the highest amino acid sequence identity of 33.75% with APH(9)-Ia. APH(9)-Ic confers resistance to spectinomycin, and a recombinant strain harboring aph(9)-Ic (pMD19-T-aph(9)-Ic/DH5α) showed a significantly increased minimum inhibitory concentration (MIC) level of spectinomycin compared with the control strains (DH5α and pMD19-T/DH5α). The results of the kinetic analysis of APH(9)-Ic were consistent with the MIC results for the recombinant pMD19-T-aph(9)-Ic/DH5α, showing the efficient catalytic activity for spectinomycin [kcat/Km ratio = (5.58 ± 0.31) × 104 M−1·s−1]. Whole-genome sequencing demonstrated that the aph(9)-Ic gene was located on the chromosome with a relatively conserved genetic environment, and no mobile genetic element was found in its surrounding region. The identification of this novel AG resistance gene will assist us in elucidating the complexity of resistance mechanisms in microbial populations.